Public Service Innovation Based on Artificial Intelligence Technology in the Protection of Citizens Abroad: A Comparative Study of Indonesia and Singapore - Arum, Anisa Kesuma; Huseini, Martani (Universitas Muhammadiyah Gorontalo, 2025)
Digital transformation in public service has encouraged governments to adopt artificial intelligence (AI) technologies to enhance service effectiveness and responsiveness, including in the context of protecting citizens abroad. This study compares Indonesia’s digital innovation through the Portal Peduli WNI and Singapore’s Digital Consular Services (DCS), focusing on technological integration, system design, and protection effectiveness. The research adopts a qualitative-descriptive approach using document analysis and in-depth interviews with officials from the Ministries of Foreign Affairs of Indonesia and Singapore. The analysis covers ten key aspects: system architecture, functions, technological infrastructure, inter-agency integration, proactive services, scalability and connectivity, key features, system orientation, emergency coordination, national system integration, and data utilization. The findings reveal that Singapore's DCS is structurally and functionally more advanced. It is designed with a modular, cloud-based architecture, integrated with national platforms such as SingPass and MyInfo, and equipped with predictive analytics, automated notifications, and digital case management. In contrast, Indonesia's Portal Peduli WNI remains reactive, lacks comprehensive integration, and has yet to support real-time, data-driven service automation. The study concludes by emphasizing the importance of adopting a whole-of-government approach, improving system interoperability, and applying AI to detect risks and accelerate emergency response for Indonesian citizens abroad. These findings are expected to serve as a foundation for more inclusive, responsive, and sustainable digital public service reform in Indonesia.